Bending the Curve of Global Freshwater Biodiversity Loss: An Emergency Recovery Plan. (19th February 2020) - Tickner, David; Opperman, Jeffrey J; Abell, Robin; Acreman, Mike; Arthington, Angela H; Bunn, Stuart E; Cooke, Steven J; Dalton, James; Darwall, Will; Edwards, Gavin; Harrison, Ian; Hughes, Kathy; et al.
Abstract: Despite their limited spatial extent, freshwater ecosystems host remarkable biodiversity, including one-third of all vertebrate species. This biodiversity is declining dramatically: Globally, wetlands are vanishing three times faster than forests, and freshwater vertebrate populations have fallen more than twice as steeply as terrestrial or marine populations. Threats to freshwater biodiversity are well documented but coordinated action to reverse the decline is lacking. We present an Emergency Recovery Plan to bend the curve of freshwater biodiversity loss. Priority actions include accelerating implementation of environmental flows; improving water quality; protecting and restoring critical habitats; managing the exploitation of freshwater ecosystem resources, especially species and riverine aggregates; preventing and controlling nonnative species invasions; and safeguarding and restoring river connectivity. We recommend adjustments to targets and indicators for the Convention on Biological Diversity and the Sustainable Development Goals and roles for national and international state and nonstate actors.